Dual-band bandpass filter based on two U-shaped defected microstrip structure - Mussa Mabrok; Zahriladha Zakaria; Yully Masrukin; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper presents design of dual-band bandpass filter by integrating conventional quarter-wavelength short circuit stubs bandpass filter with U-shaped defected microstrip structure notch filter. Based on the parametric analysis, it is found that high attenuation level can be achieved by using two U-shaped defected microstrip structure separated by specific distance. The designed circuit simulated using advanced design system and fabricated based on Roger 4350B. The simulation results are in good agreement with measured results. The designed filter covered two pass bands centered at 2.51 GHz and 3.59 GHz with 3-dB fractional bandwidth of 15.94% and 15.86%, respectively, return losses better than 15 dB, and insertion losses better than 1 dB. The designed device can be used for wireless communication applications such as WLAN and WiMAX.